Effect of Work-Related Sedentary Time on Overall Health Profile in Active vs. Inactive Office Workers - Genin, Pauline M.; Dessenne, Pascal; Finaud, Julien; Pereira, Bruno; Dutheil, Frederic; Thivel, David; Duclos, Martine (Frontiers in Public Health, 2018)
Objective. While public health strategies are developed to fight sedentary behaviors and promote physical activity, some professional activities, and especially tertiary ones, have been pointed out for their highly sedentary nature. Although workplace physical activity programs are increasingly proposed by companies to their employees in order to increase their physical activity levels, sitting and screen time remain extremely high. The main aim of this work was to compare health indicators between active and inactive tertiary employees with similar high levels of sedentariness. Secondly, we questioned the effects of a 5-month workplace physical activity program on overall health indicators among initially active and inactive tertiary employees. Methods. Anthropometric measurements, body composition (bio-impedance), physical fitness (cardiorespiratory and musculoskeletal fitness) and health-related quality of life and perception of health status (self-reported questionnaires) were assessed among 193 active and inactive tertiary employees before (T0) and after a 5-month workplace physical activity intervention (T1), composed of 2 physical sessions per week. Results. Significant improvements were found in performance of push-ups (p<0.001), back muscle strength (p<0.001) fat mass (p<0.01) and waist circumference (p<0.05) in active compared with inactive employees both at baseline and at the end of the program. Health perception (p<0.001) was significantly different between groups at T0 but not at T1. However, no significant difference was observed for fat-free mass, BMI, workplace well-being and lower and upper limbs muscle strength. The variations between T0 and T1 demonstrate that, while all the studied parameters progressed positively during the 5-month program, health perception (p<0.001), back muscle strength (p<0.05) and BMI (tendency) showed a significantly higher progression in the inactive compared with the active group. Conclusion. Health indicators might not be improved among active tertiary employees compared with inactive ones, which might be due to the high level of sedentariness characterizing their occupational task. Structured on-site physical activity programs can improve health in both initially active and inactive employees.